INOVASI PELAYANAN PERIZINAN MELALUI SI-IMUT PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA SEMARANG - Ronnyta, Regita Vania; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2020)
Public services are excellent services provided to the community as an implementationthat is the duty of the government. To meet the demands and expectations of the Semarang Cityapplicant community for licensing services that can be done easily, cheaply and quickly, theOffice of Investment and One Stop Integrated Services (DPMPTSP) of Semarang City creates aninnovative public service in the field of licensing by utilizing technology namely the InvestmentPermit System Easy and Integrated (SI-IMUT). In this study using descriptive qualitative methods and using data collection techniques such as interviews, observation and literature study. The data that has been obtained is then analyzed with qualitative data analysis techniques. Based on data obtained from the field results is explaining licensing service innovation through SI-IMUT by looking at innovation typologies that have six variables namely A new or improved service, Process Innovation, Administrative Innovation, System Innovation,Conceptual Innovation, and Radical Change of Rationality. Thus, the application of the SI-IMUThad a positive impact not only on the community of the applicant but also on the employees ofDPMPTSP Semarang City and increasing the value of investment for the City of Semarang.Keywords: Innovation, Public Service, Typology of Innovation, Public Service Innovation, SI-IMUT